PKM Pemberdayaan Orangtua Dan Guru Dalam Stimulasi Tumbuh Kembang Anak Usia 4-6 Tahun di KB TK Islam Sultan Agung 02 Kota Semarang Jawa Tengah - Fitratun Najizah; Shella Dhika R; Rafif Aydin Maheswara; Cintya Putri Anisah; Fiantika Aprianingrum; Friesca Persityara Agatha; Naufal Adib Ramadhani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Growth and development is a continuous process that occurs from conception and continues until adulthood. The pre-school period is a golden age where stimulation of all aspects of development plays an important role in subsequent developmental tasks, where 80% of children's cognitive development has been achieved at pre-school age. However, in reality there are still many parents who do not understand the importance of screening and stimulating growth and development in children. Screening is carried out to detect irregularities early so that it will be easier to overcome them. Currently, the KPSP Pro application is available, which can be accessed via smartphone, which can be used by parents to carry out independent developmental screening of their respective children. The problems currently faced by partners are the minimal knowledge of parents regarding screening and stimulating growth and development in children, the lack of utilization of the facilities that are already available for conducting screening, many parents who are not open to technology, and do not understand how to access and use applications. KPSP Pro is also unable to utilize information from screening results. The solutions offered to partners are: conducting seminars for teachers and parents regarding the importance of screening and stimulating growth and development in children, informing regarding the availability of the KPSP Pro application, teaching how to access/download the KPSP Pro application, conducting roleplays, carrying out development screening using KPSP Pro and provide an understanding regarding the use of screening results. The results of this activity showed an increase in mothers' knowledge about developmental screening of preschool-age children.